GOOGLE BISNIS, SIM DAN SIA GUNA MENETUKAN HPP SEBAGAI SARANA MENINGKATKAN PENDAPATKAN MASYARAKAT - Dwiarta, I Made Bagus (Jurnal Penamas Adi Buana, 2017)
Students create a program for the Munggu Gebang Village very potentially eligible to be shown to local and national communities. Other than that Munggu Gebang village does not have this program, therefore students assist in the creation of the account. In Google My Business account profile contains Village, human resources, and the most important is the marketed product bag, KKN-PPM method is a method in the form of training workshops and mentoring until people understand how to make or use the Internet as a medium to introduce your business. Targeted as respondents in this activity is the whole village community craftsmen bag who have a business. File and documentation obtained from the device profile data and local village village. The results achieved in this activity is to the stage of their community or are familiar with the internet and thus only the role of social media as one of support for business development.